Systematization of pedagogical activity from dialectical theory to the development of critical thinking - Aguinaga Vásquez, Silvia Josefina (2018)
The research aimed to propose the systematization of pedagogical activity from the theory of the dialectic for the de-velopment of critical thinking in the students of the fourth year of secondary education of an educational institution Lambayecana. The research was based on a sample of 87 students from section N (Experimental Group 42) and sec-tion I (Control Group: 45) in the classroom. that the level of critical thinking was identified by means of a pre-test whose diagnosis came to reflect that of the three levels of critical thinking identified by Priestley (1996) the majority of students were at the basic level. The proposal corresponds to a quasi-experimental quantitative research. The re-sults showed that after applying the proposal the majority of students in the experimental group, 30 of them managed to obtain scores that allowed him to be located in the upper level, the highest level of critical thinking. Therefore, it was concluded that the proposal to systematize the pedagogical activity based on the dialectical theory allowed to develop in the students of the fourth year of secondary education critical thinking at the highest level.